Predictability of the simple technical trading rules: An out‐of‐sample test. Issue 1 (25th May 2013) - Fang, Jiali; Jacobsen, Ben; Qin, Yafeng
Abstract: In a true out‐of‐sample test based on fresh data we find no evidence that several well‐known technical trading strategies predict stock markets over the period of 1987 to 2011. Our test safeguards against sample selection bias, data mining, hindsight bias, and other usual biases that may affect results in our field. We use the exact same technical trading rules thatBrock, Lakonishok, and LeBaron (1992) showed to work best in their historical sample. Further analysis shows that this poor out‐of‐sample performance most likely is not due to the market becoming more efficient – instantaneously or gradually over time – but probably a result of bias.